Clinical Assessment of Intravenous Endothelial Progenitor Cell Transplantation in Dogs - Seok Hee Lee; Jeong Chan Ra; Hyun Ju Oh; Min Jung Kim; Erif maha Nugraha Setyawan; Yoo Bin Choi; Jung Won Yang; Sung Keun Kang; Seung Hyup Han; Geon A. Kim; Byeong Chun Lee (Cell Transplantation, 2019)
Endothelial progenitor cells (EPCs) have been applied for cell therapy because of their roles in angiogenesis and neovascularization in ischemic tissue. However, adverse responses caused by EPC therapy have not been fully investigated. In this study, a human peripheral blood sample was collected from a healthy donor and peripheral blood mononuclear cells were separated using Ficoll-Hypaque. There were four experimental groups: 10 ml saline infusion group (injection rate; 3 ml/min), 10 ml saline bolus group (injection rate; 60 ml/min), 10 ml EPCs infusion group (2 x 10 5 cells/ml, injection rate; 3 ml/min), 10 ml EPCs bolus group (2 × 10 5 cells/ml, injection rate; 60 ml/min). Clinical assessment included physical examination and laboratory examination for intravenous human EPC transplantation in dogs. The results revealed no remarkable findings in vital signs among the dogs used. In blood analysis, platelet counts in saline infusion groups were significantly higher than in the EPC groups within normal ranges, and no significant differences were observed except K + , Cl – and blood urea nitrogen/urea. In ELISA assay, no significant difference was observed in serum tumor necrosis factor alpha. The serum concentration of vascular endothelial growth factor was significantly higher in EPC groups than in saline groups, and interleukin 10 was significantly up-regulated in the EPC infusion group compared with other groups. In conclusion, we demonstrated that no clinical abnormalities were detected after intravenous transplantation of human EPCs in dogs. The transplanted xenogenic EPCs might be involved in anti-inflammatory and angiogenic functions in dogs.